PENGARUH CORPORATE SOCIAL RESPONSIBILITY, BRAND IMAGE, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SURAT KABAR SUARA MERDEKA DI KOTA SEMARANG - Nurita Hertina Novia Sari; Hari Susanta Nugraha; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2014)
Newspaper is a media for the society to gain some information about what happens around them from a reliable resource. Newspaper held a significant roles in reporting event around the society or simply a channel for expressing people’s Ideas through the its contents . PT. Suara Merdeka Press is a newspaper company which practicing Corporate Social Responbility program in it, further this program used to interact with people and build reputation for the company. Beside CSR, Suara Merdeka also build their Brand Image that recognizable for the people and proper Price through news material’s quality. All of these concept are meant to create buying decision from the society. The goal of this research is to analize the impact of corporate social responsibility, brand image, and price.This research type is Nonprobability sampling with total 100 respondents and the population is Suara Merdeka Consumer. Sampling technic used is accidental sampling. Analysis used here is double regression analysis, Hipothesis testing using T test & F test, Determination Coefficient and cross tabs. From regression anaysis generated Y  =  2,953 + 0,113X1  + 0,074X2 + 0,632X3. Where Purchase Decision Variable (Y), Corporate Social Responsibility  (X1),  Brand Image (X2) and Price (X3).  Hipothesis testing using T test and F test showed that observed three independent variables significantly impacting the purchase decision dependent variable. Author would like to suggest that Suara Merdeka has to improve their CSR programme, maintain their brand image so the consument still buying this newspaper, and Price should be adjusted to the quality of the news. Last thing Suara Merdeka should aware of the consument decision for subscribing or simply buying this newspaper.